Механізація вирощування жита з модернізацією зернової сівалки - Лазоренко, Валерій Вікторович; Lazorenko, Valerii (ЦНТУ, 2023)
В роботі удосконалено технологію вирощування жита. Мета роботи – підвищення ефективності сівби насіння жита. У дипломному проектіпроведено аналіз базової технології вирощування жита і запропоновано удосконалення. Розраховано склад широкозахватного посівного агрегату і складено операційно-технологічну карту на сівбу насіння жита. Крім того, в роботі удосконалено сівалку – для підвищення чіткості створення маркерного сліду, запропоновано використати зубчастий диск маркера. The work improved the technology of growing rye. The purpose of the work is to increase the efficiency of sowing rye seeds. The diploma project analyzed the basic technology of growing rye and proposed improvements. The composition of the wide-reaching sowing unit was calculated and an operational-technological map for sowing rye seeds was drawn up. In addition, the planter was improved in the work - to increase the clarity of creating a marker trail, it was suggested to use a toothed disk of the marker.
Mechanization of rye cultivation with modernization of grain seeder
Keywords: висівний апарат; жито; маркер; sowing device; rye; marker